2022
DOI: 10.1186/s13287-022-03140-3
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 and Nell-1 in dental follicle progenitor cells regulate bone remodeling and tooth eruption

Abstract: Dental follicles are necessary for tooth eruption, surround the enamel organ and dental papilla, and regulate both the formation and resorption of alveolar bone. Dental follicle progenitor cells (DFPCs), which are stem cells found in dental follicles, differentiate into different kinds of cells that are necessary for tooth formation and eruption. Runt‐related transcription factor 2 (Runx2) is a transcription factor that is essential for osteoblasts and osteoclasts differentiation, as well as bone remodeling. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 103 publications
0
11
0
8
Order By: Relevance
“…The impaired osteogenic potential of SHED from patients with CCD. have mainly focused on the mechanism of dental replacement (Qin et al, 2019;Xin et al, 2022;Zeng et al, 2022). However, the clinical features of severe caries and early tooth loss, which also influence the oral and mental health of individuals with CCD, have been received little attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impaired osteogenic potential of SHED from patients with CCD. have mainly focused on the mechanism of dental replacement (Qin et al, 2019;Xin et al, 2022;Zeng et al, 2022). However, the clinical features of severe caries and early tooth loss, which also influence the oral and mental health of individuals with CCD, have been received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…As RUNX2 is the causative gene for CCD and is important in tooth formation, different types of cells with heterozygous mutations of RUNX2 show diverse dysfunction, leading to various oral manifestations when mutated. For instance, dental follicle cells with RUNX2 mutations show weaker osteogenesis and osteoclastic ability, resulting in tooth eruption and alveolar bone remodeling difficulties, and periodontal ligament cells with RUNX2 mutations demonstrate an affected balance between osteoblast and osteoclast activity, leading to tooth eruption difficulties and deciduous tooth retention (Komori et al, 1997;Sun et al, 2016;Zeng et al, 2022). In the present study, SHED obtained from the proband showed a weaker capacity for proliferation and osteogenesis than SHED obtained from healthy individuals (Figures 5, 6), consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there may have been an immunosuppressed population of cells in both tissues. Studies have shown that cytokines secreted by dental follicle cells inhibited lymphocyte proliferation ( 36 ), and osteoprotegerin secreted by dental follicle cells inhibited monocyte recruitment and osteoclast formation ( 37 ). Despite the need to form an osteoclastic resorption channel during tooth germ development and eruption, this seems consistent given the simultaneous alveolar bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…76 This protein is essential for osteoblasts and osteoclasts differentiation. 77 Some research also mentions that upregulated Runx2 and Sox6 also contribute to bone formation, especially for chondrocyte differentiation. 78 Related to increased runx2 expression after supplementation of GSE on the arthritis model, 53 the supplementation also decreased the HIF-1α expression in the alveolar bone.…”
Section: Discussionmentioning
confidence: 99%